Hemetsberger–Knittel and Ketcham Synthesis of Heteropentalenes with Two (1:1), Three (1:2)/(2:1) and Four (2:2) Heteroatoms - Zita Tokárová; Renáta Gašparová; Natália Kabaňová; Marcela Gašparová; Róbert Balogh (Reactions, 2023)
The synthetic methods leading to furo[3,2-b]pyrroles and thiazolo [5,4-d]thiazoles are reviewed herein. Furo-, thieno- and seleno [3,2-b]pyrroles are related to heteropentalenes, containing two heteroatoms in the entire structure, one each per core. The synthetic approach follows the Hemetsberger–Knittel protocol covering three reaction steps—the nucleophilic substitution of halogen-containing aliphatic carboxylic acid esters, Knoevenagel condensation and, finally, thermolysis promoting the intramolecular cyclocondensation to O,N-heteropentalene. The Hemetsberger–Knittel reaction sequence is also known for the preparation of O,N-heteropentalenes with three heteroatoms (2:1) and their sulphur and selen heteroatoms containing structural analogues and bispyrroles. The synthetic approach towards thiazolo [5,4-d] thiazoles represents a more straightforward route, according to the Ketcham cyclocondensation. Proceeding with the Ketcham process is more challenging since it occurs stepwise and the formation of by-products is obvious. Thiazolo [5,4-d]thiazole is a representative of the aromatic heteropentalene with four heteroatoms in the structure—twinned N and S, two for each of the five-membered rings. The synthetic approaches towards those particular heteropentalnes have been chosen as a consequence of our ongoing research dealing with the design, synthesis and applications of substituted furo [3,2-b]pyrroles and thiazolo [5,4-d]thiazole-based derivatives. While the furopyrroles are known for their pharmacological activity, thiazolothiazoles have become of interest to materials science. We are aware that from a “bank” of existing compounds/procedures not all are presented in this review, and we apologise to respective groups whose research have not been objectively included.